Do outcomes of near syncope parallel syncope? - Cernuschi, Giulia; Bonzi, Mattia; Fiorelli, Elisa; Birocchi, Simone (The American journal of emergency medicine, 2012)
[...]we wonder if comparing patients presenting with near syncope to patients with syncope from a different cohort [5] could lead to any bias. [...]we found that the outcomes considered in these 2 studies are different.